The Impact of Instagram Social Media Marketing on MSME Product Brand Awareness Call for Coffee - Muh. Dewanata Anugrah Setya; Tongam Sirait (Journal of World Science, 2024)
This study aims to determine and analyze the effect of social media marketing instagram on brand awareness of umkm serum coffee products. The method in this research is descriptive and causal. The population in this study were Seruan Coffee Instagram social media followers. Determination of the research sample using the slovin formula, so that 233 people were obtained. The results showed that entertainment, with a value of 4.28 and a regression coefficient of 0.360, had a positive and significant effect on brand awareness. Interaction, with a value of 4.18 and a regression coefficient of 0.491, also shows a positive and significant influence. Similarly, informativeness, with a value of 4.1 and a regression coefficient of 0.670; advertisement, with a value of 4.15 and a regression coefficient of 0.488; and e-word of mouth, with a value of 4.07 and a regression coefficient of 0.818, all have a significant influence on brand awareness. Overall, marketing on Instagram social media, which includes entertainment, interaction, informativeness, advertising, and e-word of mouth, is rated very well by respondents. The results of the analysis show that the variables of Social Media Marketing and Brand Awareness are rated very well and have a partial and simultaneous effect on brand awareness of MSME products, with a significant t-count (5.799 > 1.649) and f-count (178.243 > 2.21). This study implies that to increase brand awareness, Kopi Seruan MSMEs must continue to optimize their social media marketing strategies, especially in entertainment, interaction, informativeness, advertising, and e-word of mouth.